2023
DOI: 10.3390/antiox12091685
|View full text |Cite
|
Sign up to set email alerts
|

Selenomethionine Attenuated H2O2-Induced Oxidative Stress and Apoptosis by Nrf2 in Chicken Liver Cells

Lingyu Xie,
Yibin Xu,
Xiaoqing Ding
et al.

Abstract: Earlier studies have shown that selenomethionine (SM) supplements in broiler breeders had higher deposition in eggs, further reduced the mortality of chicken embryos, and exerted a stronger antioxidant ability in offspring than sodium selenite (SS). Since previous studies also confirmed that Se deposition in eggs was positively correlated with maternal supplementation, this study aimed to directly investigate the antioxidant activities and underlying mechanisms of SS and SM on the chicken hepatocellular carcin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 62 publications
(89 reference statements)
0
5
0
Order By: Relevance
“…Cao et al [75] and Sahin et al [76] found that HS resulted in a decline in mRNA expression level of Nrf2, SOD, GST, HO-1, etc. Conversely, previous studies showed that selenomethionine supplements enhanced the level of T-AOC and the ability of T-SOD in H 2 O 2 -induced liver damage model [77]. Wan et al [78] verified that selenomethionine could improve the glutathione system to enhance the antioxidant capacity of liver.…”
Section: Effects Of Dietary Senps-aos Supplementation On the Liver Of...mentioning
confidence: 94%
“…Cao et al [75] and Sahin et al [76] found that HS resulted in a decline in mRNA expression level of Nrf2, SOD, GST, HO-1, etc. Conversely, previous studies showed that selenomethionine supplements enhanced the level of T-AOC and the ability of T-SOD in H 2 O 2 -induced liver damage model [77]. Wan et al [78] verified that selenomethionine could improve the glutathione system to enhance the antioxidant capacity of liver.…”
Section: Effects Of Dietary Senps-aos Supplementation On the Liver Of...mentioning
confidence: 94%
“…Inorganic selenium, particularly sodium selenite, constitutes the primary source, while organic selenium is predominantly derived from yeast selenium, with its principal form being selenomethionine (SeMet) [ 11 ]. Compared with sodium selenite, SeMet exerts a range of important advantages, including less toxicity and higher bioavailability [ 12 ]. SeMet could replace methionine to incorporate into protein synthesis or can be directly converted into selenocysteine through the trans-sulfuration pathway [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with sodium selenite, SeMet exerts a range of important advantages, including less toxicity and higher bioavailability [ 12 ]. SeMet could replace methionine to incorporate into protein synthesis or can be directly converted into selenocysteine through the trans-sulfuration pathway [ 12 ]. Indeed, it is reported that SeMet supplementation enhanced the antioxidant capacity, immunity, and selenium deposition in pigs when compared to sodium selenite [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, Se-Met was reported to mitigate oxidative stress induced by DON in the small intestinal epithelium of C57BL/6 mice [16]. Most recently, Se-Met has been demonstrated to exert protective effects for mitigating oxidative stress in poultry through the Nrf2 pathway [17][18][19]. Xie et al (2023), using an in vitro model of chicken liver cells, demonstrated that Se-Met mitigated hepatic oxidative stress caused by hydrogen peroxide challenge [17].…”
Section: Introductionmentioning
confidence: 99%
“…Most recently, Se-Met has been demonstrated to exert protective effects for mitigating oxidative stress in poultry through the Nrf2 pathway [17][18][19]. Xie et al (2023), using an in vitro model of chicken liver cells, demonstrated that Se-Met mitigated hepatic oxidative stress caused by hydrogen peroxide challenge [17]. Li et al (2024) also found that Se-Met effectively decreased oxidative injury associated with Nrf2 pathway regulation of laying hens challenged with lipopolysaccharide [18].…”
Section: Introductionmentioning
confidence: 99%